Corporate Social Responsibility In The Context Of Sarawak Digital Economy: An Organisational Sensemaking Analysis In Malaysia - Ahmad, Dayang Aizza Maisha Abang (2021)
Corporate Social Responsibility (CSR) has proven to be one of the innovative mechanism that has been extensively used by authorities and organisations around the globe in tackling and coping with social challenges and economic pursuits. This research takes on the pioneering attempt in analysing the CSR sensemaking process of an organisation’s adaptive and context-related approach to accommodating the emphasis and direction of the Sarawak Digital Economy (SDE) environment. The conduct of this study is developed upon three objectives; that is 1) to interpret the Organisation’s CSR; 2) to analyse the Organisation’s sensemaking process of CSR in response to the implementation of SDE; 3) to interpret the Organisation’s CSR in the context of SDE. For this purpose, a single case study approach is applied in analysing the Sarawak Information Systems Sdn. Bhd. (SAINS) long-standing CSR programme; in which is prominently known for its contribution in bridging digital divide and improving the socioeconomic development gap between the rural and urban populace in Sarawak. Centred upon the use of Weick’s (1995) Sensemaking properties and Carroll’s (1991) CSR Pyramid; findings from the in-depth interview, focus groups and document analysis have contributed in redefining Carroll’s four-part components and the placement of priorities based on the perceived importance assigned by the organisation understudy (i.e. ‘philanthropic’ being the most important, followed by economic, legal, and ethical).